From beginner to expert, IDNLearn.com has answers for everyone. Ask your questions and receive comprehensive and trustworthy answers from our experienced community of professionals.

How many solutions does this equation have?

–2b − 9 = –b


Sagot :

Answer:

b= -3

b=3/2=1.500

Step-by-step explanation:

step 1 . b • (2b + 3) -  9  = 0

Step-2 : Find two factors of  -18  whose sum equals the coefficient of the middle term, which is   3 .

     -18    +    1    =    -17  

     -9    +    2    =    -7  

     -6    +    3    =    -3  

     -3    +    6    =    3

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above,  -3  and  6  

                    2b2 - 3b + 6b - 9

Step-4 : Add up the first 2 terms, pulling out like factors :

                   b • (2b-3)

             Add up the last 2 terms, pulling out common factors :

                   3 • (2b-3)

Step-5 : Add up the four terms of step 4 :

                   (b+3)  •  (2b-3)